1995
DOI: 10.1074/jbc.270.22.13084
|View full text |Cite
|
Sign up to set email alerts
|

The Polyprotein Precursor to the Euglena Light-harvesting Chlorophyll a/b-binding Protein Is Transported to the Golgi Apparatus Prior to Chloroplast Import and Polyprotein Processing

Abstract: The major Euglena thylakoid protein, the light harvesting chlorophyll a/b-binding protein of photosystem II (pLHCPII) is synthesized in the cytoplasm as a polyprotein precursor composed of a 141 amino acid presequence containing a signal peptide domain followed by eight mature LHCPIIs covalently linked by a decapeptide. To determine the transport route from cytoplasm to chloroplast and the site of polyprotein processing, Euglena was pulse labeled with [35S]sulfate, organelles separated on sucrose gradients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 53 publications
1
78
1
Order By: Relevance
“…Proteins destined for all known secondary plastids commence their journey in the ER, but mechanisms for targeting from the ER to secondary plastids differ. In Euglenoids (green lineage), proteins are targeted to the chloroplast via the Golgi and contain a stop-transfer sequence after the transit peptide (Sulli et al, 1999;Sulli and Schwartzbach, 1995). In the case of enslaved chloroplasts derived from a red alga, CavalierSmith has suggested that proteins traffic directly from the ER (Cavalier-Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins destined for all known secondary plastids commence their journey in the ER, but mechanisms for targeting from the ER to secondary plastids differ. In Euglenoids (green lineage), proteins are targeted to the chloroplast via the Golgi and contain a stop-transfer sequence after the transit peptide (Sulli et al, 1999;Sulli and Schwartzbach, 1995). In the case of enslaved chloroplasts derived from a red alga, CavalierSmith has suggested that proteins traffic directly from the ER (Cavalier-Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Presequences of nuclear-encoded plastid proteins of these organisms are also found to have a bipartite structure (38 -40). For Euglena there is evidence that precursor proteins might be translated at cytosolic ER membranes first and subsequently get transported to the plastids via the Golgi system (41,42). The general presence of N-terminal signal peptide domains in precursors of nucleus-encoded plastid proteins of cells with three-or four-membrane plastids indicates that after secondary endosymbiosis and subsequent transfer of the respective genes to the nucleus of the host cell, the pathway across the ER membranes was utilized to target proteins into the newly acquired plastids.…”
Section: Discussionmentioning
confidence: 99%
“…pLHCPll is synthesized on membrane-bound polysomes (Kishore and Schwartzbach, 1992), and immunoelectron microscopy localizes LHCPll to the Golgi apparatus before LHCPll accumulation in thylakoids Schiff et al, 1991). In vivo pulse-chase experiments have shown that pLHCPll is transported as a membrane-bound polyprotein from the ER to the Golgi apparatus and from the Golgi apparatus to the chloroplast (Sulli and Schwartzbach, 1995).…”
Section: Introductionmentioning
confidence: 99%